Cyclophosphamide Pharmacogenomic Variation in Cancer Treatment and Its Effect on Bioactivation and Pharmacokinetics - Ibrahim El-Serafi; Sinclair Steele (Advances in Pharmacological and Pharmaceutical Sciences)
Cyclophosphamide (Cy) is a prodrug that is mainly bioactivated by cytochrome P450 (CYP) 2B6 enzyme. Several other enzymes are also involved in its bioactivation and affect its kinetics. Previous studies have shown the effect of the enzymes’ genetic polymorphisms on Cy kinetics and its clinical outcome. These results were controversial primarily because of the involvement of several interacting enzymes in the Cy metabolic pathway, which can also be affected by several clinical factors as well as other drug interactions. In this review article, we present the effect of CYP2B6 polymorphisms on Cy kinetics since it is the main bioactivating enzyme, as well as discussing all previously reported enzymes and clinical factors that can alter Cy efficacy. Additionally, we present explanations for key Cy side effects related to the nature and site of its bioactivation. Finally, we discuss the role of busulphan in conditioning regimens in the Cy metabolic pathway as a clinical example of drug-drug interactions involving several enzymes. By the end of this article, our aim is to have provided a comprehensive summary of Cy pharmacogenomics and the effect on its kinetics. The utility of these findings in the development of new strategies for Cy personalized patient dose adjustment will aid in the future optimization of patient specific Cy dosages and ultimately in improving clinical outcomes. In conclusion, CYP2B6 and several other enzyme polymorphisms can alter Cy kinetics and consequently the clinical outcomes. However, the precise quantification of Cy kinetics in any individual patient is complex as it is clearly under multifactorial genetic control. Additionally, other clinical factors such as the patient’s age, diagnosis, concomitant medications, and clinical status should also be considered.